Stakeknife's dirty war : the inside story of Scappaticci, the IRA's Nutting Squad and the British spooks who ran the war / Richard O'Rawe. - O'Rawe, Richard (Merrion Press, 2023)
Freddie 'Stakeknife' Scappaticci was one of the most notorious members of the Provisional IRA. He personally executed two suspected informers and condemned at least thirty-seven more to death. But he was also working as an informer for British intelligence. This is the shocking story of his double life.